Review of the New Age Religions: Atheism, Secularism and Scientism (International Journal of Innovative Research in Engineering & Management, 2021)
The article is about faith and conviction for improving the  human usage of fundamental freedoms for all people from the  world's networks. In this study, the question of religion and  belief in the turn of events is explained. This article included  scientific methods for analysts to refer to books they were  debating (religion and belief in the human turn of events),  which they later analyzed and explained in amazing fashion. This study is considered a doctrinal study, in which the expert  depended on reports, books and updates and subjected them to  logical research to the ideal results. With regard to the subtopics  to be discussed in this review, they are misunderstandings about  the Vedas and illuminate the overall picture of what is the new  age religion, its impact on the current generation and what this  "secularism" guardian is about. At this point, the result will be  integrated, the most important being that the globe needs cooperation for compassionate interests and human turn of  events.
Keywords: Atheism; New Age Religion; Religion; scientism; Secularism; Vedas